Os novos modelos de gestão: análise e algumas práticas em empresas brasileiras - Pereira, Heitor José (1995)
The main purpose of this thesis is to contribute to understanding the new approaches of management. The study is composed of three parts: the first describes the evolution of the ‘corporate eras’, since the Second Industrial Revolution (‘mass production’) until the lnformation Society (‘competitivity era’); the second part is a description of a conceptual framework of the new approaches of management, including the following: japanese management; participative management; entre/intrapreneurial management; holistic management; and virtual corporation. Finally, the third partis a report of three case studies about the evolution of the management in brazilian innovative companies. Thus, the study is a descriptive research. The main conclusion is that the brazilian companies need rapidly to cope their managerial models to the new approaches to survive in the turbulent nineties. The study resulted in a set of recommendations about the introduction of the new approaches of management in brazilian companies.